2012
DOI: 10.1186/1471-2377-12-117
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ischemic stroke; results from 9 years of follow-up in a population based cohort of Iran

Abstract: BackgroundData about the risk factors of stroke are sparse in the Middle East populations. We aimed to determine the potential risk factors and their population attributable fraction (PAF) for stroke in an Iranian population.MethodsA cohort Study consisted of 1089 men and 1289 women, with mean (SD) ages of 61.1(7.6) and 59.0(6.7) years, respectively. Cox regression was implemented to estimate the hazard ratio (HR) of each risk factor for stroke events in a stepwise method. We calculated a multivariate adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 26 publications
(40 reference statements)
3
53
2
Order By: Relevance
“…Also, it has been reported that, among smokers, the effect of risk factor accumulation on the incidence of CVD was more apparent (Iso et al, 2007). Recently, we showed that smoking had a significant risk for stroke events and had a population attributable fraction of $13% among the Iranian population (Fahimfar et al, 2012). However, no data was available on the effect of smoking on mortality and CVD events in Iran.…”
Section: Discussionmentioning
confidence: 97%
“…Also, it has been reported that, among smokers, the effect of risk factor accumulation on the incidence of CVD was more apparent (Iso et al, 2007). Recently, we showed that smoking had a significant risk for stroke events and had a population attributable fraction of $13% among the Iranian population (Fahimfar et al, 2012). However, no data was available on the effect of smoking on mortality and CVD events in Iran.…”
Section: Discussionmentioning
confidence: 97%
“…A cohort study of Iran [16] found that hypertension (hazard ratio 3.03, 95% CI 1.76-5.22) was independently associated with an increased risk of stroke events in the total population. A meta-analysis also found a continuous and graded relationship between blood pressure and stroke risk in many populations, with higher levels of blood pressure conferring greater risks of stroke in hypertensive and normotensive individuals [17].…”
Section: Discussionmentioning
confidence: 98%
“…It is a major cause of mortality worldwide. 2,7,19 It is the leading cause of death only next to cancer. 11,29,33 There are three types of strokes, which include Ischemic (88%) Hemorrhagic (12%) and Transient (rare type).…”
Section: Introductionmentioning
confidence: 99%